The effectiveness of selected electrode In electrocoagulation process In treating palm oil mill Effluent (POME) - Muna Amirah Mohamad (School of Environmental Engineering, University Malaysia Perlis, 2012)
Palm oil mill effluent (POME) from industrial activities may affect environment and human health due to high amount of Biochemical Oxygen Demand(BOD), Chemical Oxygen Demand (COD) and Total Suspended solid (TSS). Many methods have been used to remove those pollutants but they are high in cost,produce large amount of sludge, require large land area electricity. This study was performed to investigate the behaviour of electrocoagulation of palm oil mill effluent (POME). This study was focusing on the effect of electrocoagulation of POME due to current density, sample concentration and duration of current flow.Simple electrochemical cell was prepared by using galvanized iron (GI) and Aluminum plate electrode. The effectiveness of the method was determined by measuring percentage of pollutant removal. It is found that electrocoagulation of POME was directly proportional to current density, duration of electric current flow. Current density, duration and concentration does affecting the percentage of pollutant removal. Aluminum electrodes are the best in removing TSSat current density 120A/mp2s,duration 60 minutes,concentration 25 %.GI electrodes are the best in removing TSS at current density 240A/mp2s,duration of 60 minutes,concentration of sample is 100%.Aluminum electrodes are the best in removing Total Phosphorus at current density 240A/mp2s,duration 20 minutes,concentration 25%.GI electrodes are the best in removing Total Phosphorus at current density 120A/mp2s,duration 60 minutes,concentration 25%.